087 Communicating in challenging situations: enhancing professional conversations in a tertiary paediatric centre. (December 2018) - Parish, E; Wykurz, G; Sharma, S
Abstract : Background: Great Ormond Street Hospital has a high turnover of staff, including those temporarily in the organisation alongside established international experts. This environment, while stimulating, is potentially intimidating. Evidence supports good teamwork and inter-professional skills contribute to better patient outcomes and improved staff morale. We wanted to develop free-to-user training to enhance communication and teamwork between colleagues in clinical settings, breaking down silo working and hierarchies. The Post-Graduate Medical Education (PGME) department invited an external facilitator to support a course on 'Professional Conversations'. Utilising the experience of clinical staff, educators, managers, and a group of specialist actors we co-created content. The course runs over two days, a month apart. Participant's complete pre-course questionnaires identifying situations they find challenging. On Day 1 each participant is supported to craft a personalised scenario based on their experience. Communication simulation is followed by structured debrief and reflection. Day 2 offers time to reflect on the use of skills in practice through collaborative learning groups. Results: The course has run 3 times with 52 participants and excellent delegate feedback. 83% provided feedback: all agree or strongly agree, the course was relevant. 100% stated it would change their practice. It is not possible to directly correlate improvements in staff retention and patient experience. In qualitative feedback, participants identified the value of a 'safe' space to discuss challenges in inter-professional communication that hinder care. Discussion and conclusions: We are impressed by uptake in department's not initially targeted (social work, play specialists and research-based specialities). We spent time developing a faculty that spans professions, including actors, whose observations and insights have developed unexpected elements of the course (breathing and co-ordination exercises to enhance self-awareness, highlight body language, peripheral awareness and anticipation). Mixed-method teaching provides a safe space for colleagues to develop trust and prepare themselves before potentially difficult encounters with colleagues.